Virgin Territory: Configuring Female Virginity in Early Christianity By J. K. Lillis (2023) - Sellick, Jeannie (Body and Religion, 2025)
Virgin Territory: Configuring Female Virginity in Early Christianity By J. K. Lillis (2023) Oakland: University of California Press, xvi + 222pp.